Mechanisms of the Testis Toxicity Induced by Chronic Exposure to Mequindox - Qianying Liu; Zhixin Lei; Anxiong Huang; Qirong Lu; Xu Wang; Saeed Ahmed; Ihsan Awais; Zonghui Yuan; Zonghui Yuan; Zonghui Yuan (Frontiers Media S.A., 2017)
Mequindox (MEQ) is a synthetic antimicrobial agent widely used in China since the 1980s. Although the toxicity of MEQ is well recognized, its testis toxicity has not been adequately investigated. In the present study, we provide evidence that MEQ triggers oxidative stress, mitochondrion dysfunction and spermatogenesis deficiency in mice after exposure to MEQ (0, 25, 55, and 110 mg/kg in the diet) for up to 18 months. The genotoxicity and adrenal toxicity may contribute to sperm abnormalities caused by MEQ. Moreover, using LC/MS-IT-TOF analysis, two metabolites, 3-methyl-2-(1-hydroxyethyl) quinoxaline-N4-monoxide (M4) and 3-methyl-2-(1-hydroxyethyl) quinoxaline-N1-monoxide (M8), were detected in the serum of mice, which directly confirms the relationship between the N→O group reduction metabolism of MEQ and oxidative stress. Interestingly, only M4 was detected in the testes, suggesting that the higher reproductive toxicity of M4 than M8 might be due to the increased stability of M4-radical (M4-R) compared to M8-radical (M8-R). Furthermore, the expression of the blood-testis barrier (BTB)-associated junctions such as tight junctions, gap junctions and basal ectoplasmic specializations were also examined. The present study demonstrated for the first time the role of the M4 in testis toxicity, and illustrated that the oxidative stress, mitochondrion dysfunction and interference in spermatogenesis, as well as the altered expression of BTB related junctions, were involved in the reproductive toxicity mediated by MEQ in vivo.